Critical analysis of a simplified Fuhrman grading scheme for prediction of cancer specific mortality in patients with clear cell renal cell carcinoma – Impact on prognosis. Issue 3 (March 2016) - Becker, A.; Hickmann, D.; Hansen, J.; Meyer, C.; Rink, M.; Schmid, M.; Eichelberg, C.; Strini, K.; Chromecki, T.; Jesche, J.; Regier, M.; Randazzo, M.; et al.
Abstract: Introduction and objectives: The traditional 4-tiered Fuhrman grading system (FGS) is widely accepted as histopathological classification for clear cell renal cell carcinoma (ccRCC) and has shown prognostic value. As intra- and inter-observer agreement are sub-optimal, simplified 2- or 3-tiered FGSs have been proposed. We aimed to validate these simplified 2- or 3-tiered FGSs for prediction of cancer-specific mortality (CSM) in a large study population from 2 European tertiary care centers. Methods: We identified and followed-up 2415 patients with ccRCC who underwent radical or partial nephrectomy in 2 European tertiary care centers. Univariable and multivariable analyses and prognostic accuracy analyses were performed to evaluate the ability of several simplified FGSs (i.e. grades I + II vs., grades III + IV, grades I + II vs. grade III and grade IV) to predict CSM. Results: Independent predictor status in multivariate analyses was proved for the simplified 2-tiered FGS (high-grade vs. low-grade), for the simplified 3-tiered FGS (grades I + II vs. grade III and grade IV) as well as for the traditional 4-tiered FGS. The prognostic accuracy of multivariable models of 77% was identical for all tested models. Prognostic accuracy of the model without FG was 75%. Conclusions: A simplified 2- or 3-tiered FGS could predict CSM as accurate as the traditional 4-tiered FGS in a large European study population. Application of new simplified 2- or 3-tiered FGS may reduce inter-observer-variability and facilitate clinical practice without compromising the ability to predict CSM in ccRCC patients after radical or partial nephrectomy.